Elliptic pseudodifferential operators in the improved scale of spaces on a closed manifold - Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We study linear elliptic pseudodifferential operators in the improved scale of functional Hilbert spaces on a smooth closed manifold. Elements of this scale are isotropic Hörmander-Volevich-Paneyakh spaces. We investigate the local smoothness of a solution of an elliptic equation in the improved scale. We also study elliptic pseudodifferential operators with parameter.